Effects of Islamic Scientist History on Seventh Graders' Understandings of Nature of Science in a Thai Islamic Private School - Safkolam, R.; Khumwong, P.; Pruekpramool, C.; Hajisamoh, A. (Jurnal Pendidikan IPA Indonesia, 2021)
Societies and cultures influence students' understandings of the nature of science (NOS). An approach to promote an accurate understanding of the nature of science is to manage the learning based on students' contexts through the integration of their social, cultural, and religious stories. Hence, this study investigated the pedagogical effects of Islamic scientist history on seventh graders' understandings of the nature of science in an Islamic private school, Yala Province, Thailand. Through a mixed-methods convergent design, data were collected from 30 seventh graders in an Islamic private school of Yala who were selected through a convenience sampling. The instruments were 1) a NOS questionnaire and 2) a semi-structured interview on the understanding of the nature of science. The quantitative data were statistically analyzed using mean, standard deviation, and a dependent t-test. The qualitative data were analyzed through content analysis and categorized into three groups based on the views of the nature of science: informed views (IV), transitional views (TV), and naive views (NV). Results revealed that the students who learned from the history of Islamic scientists had gained higher mean scores on the understanding of the nature of science at the .05 significance level and transformed their views from transitional (TV) and naive (NV) to informed (IV) in every aspect of the nature of science. This can be summarized that applying the history of Islamic scientists with the explicit reflective NOS teaching is practical in Islamic private school. To make this change happen in the unique school context, science teachers must devote time to analyzing the NOS hidden in the history of Islamic scientists. In addition, another Islamic context, such as local Islamic wisdom, could also promote the understanding of the NOS for students in private Islamic schools.